Pengaruh Syariah Marketing, Trust dan Complaint Handling terhadap Customer Financing Loyalty pada KSPS BMT Surya Sleman - Riza Kharisma; Abdul Salam; Rico Saktiawab Jang Jaya (Universitas Alma Ata, 2017)
This study aims to test and determine the influence of sharia marketing, trust and complaint handling to customer financial loyalty. Subjects in this study are active financing customers at KSPS BTM Surya PDM Sleman in 2017. There was 65 financing customers as this research sample, selected by using purposive sampling method. This study aims to prove, (1) does sharia marketing have a positive effect on customer financial loyalty, (2) does the trust have a positive effect on customer financial loyalty, (3) does the complaint handling have positive effect on customer financial loyalty, (4) does sharia marketing, trust and complaint handling have simultaneous effect on customer financial loyalty.Based on t test results, it can be seen that the variables of marketing sharia obtained t value of 1.222 <1.670, thus it can be concluded that sharia marketing has no significant effect on customer financial loyalty. Trust variable obtained t value 2.248> 1.670 thus it can be concluded that trust significantly influence the customer financial loyalty. Complaint handling variable obtained t value arithmetic 3.208> 1.670 thus can be concluded that complaint handling had significant effect on customer financial loyalty. While the hypothesis testing can be seen that f arithmetic is 64,710 while f table 2,76 with significant level 0,000> 0,05. This means that all independent variables can influence the dependent variable all together toward customer financial loyalty.Keywords: Sharia Marketing, Trust, Complaint Handling, Customer Financial Loyalty